Uji Validitas Dan Reliabilitas Prototipe Aplikasi "SICEPAT Anak" Menggunakan System Usability Scale (SUS) Dan Technology Acceptance Model (TAM) - Edi Sanjana, I Wayan; Krisnandari D, Anak Agung Istri Wulan; Pertama, Pande Putu Gede Putra (Jurnal Gema Keperawatan, 2025)
The pre-hospital emergency management of pediatric patients can be challenging for ambulance nurses when providing emergency care. This situation can arise due to a  lack of specific protocols and limited experience with pediatric cases. Digitalization through mobile-based applications is needed as a clinical decision aid. In developing a mobile application prototype, it is necessary to conduct validation and reliability testing by experts and users to improve suitability of use before implementation. This study aims to test the validity and reliability of the “SiCEPAT Anak” application prototype using the System Usability Scale (SUS) and Technology Acceptance Model (TAM) instruments. This study used a descriptive cross-sectional study design conducted on 30 ambulance nurses selected using purposive sampling. Content validity was tested through Face Validity by experts in the fields of Information Technology Systems and Emergency Nursing, while reliability was measured using the Cronbach's Alpha coefficient. The majority of respondents had a nursing education level (63.3%) and were in the adult age category. The reliability test results showed a Cronbach's Alpha value of 0.735 for SUS and 0.837 for TAM. The measurement of usability and technology acceptance in the “SiCepat Anak” application prototype from the statistical test results proved to be reliable. The application is considered to have good internal consistency, is easy to use, and is well-accepted by nurses as an aid for handling pediatric emergencies. These findings contribute to clinical decision-making and guide the development of advanced features to enhance the quality and safety of pre-hospital pediatric care.